Is Care by Grandparents or Parents Better for Children's Non-cognitive Skills? Evidence on Locus of Control from China - Xiang Ao; Xuan Chen; Zhong Zhao (Institute of Labor Economics (IZA), 2021)
This study investigates the effect of grandparental care on children's locus of control (LOC), which is an important non-cognitive skill that affects children's future development. We use data from the China Family Panel Studies, which is a nationally representative survey, and employ instrumental variables to address the endogeneity of family childcare choice. We find that children in the care of their grandparents have more external LOC than children in the care of their parents do; that is, they are more likely to attribute individual success to external factors, such as luck, fate, and family background. This finding is robust to different measures of grandparental care and different model specifications. We further examine the potential mechanisms underlying this effect. Grandparents have more external LOC than parents do, which can affect children's LOC through intergenerational transmission of LOC. Their parenting attitudes and styles are also different from parents' in that grandparents take less responsibility for children's academic performance than parents do and are less strict with children. In addition, grandparental care induces adverse effects on children's family environment.
Keywords: J13; 330; intergenerational childcare; non-cognitive skill; locus of control